A customizable smart shoes with location tracking function for the elderly. (2019) - Kit Cheng, Wai; Lok Lam, Ho; Lin, Fei; Ge, Ming
Abstract: With the aging population becoming increasingly severe, one of the outstanding problems focuses on the elderly foot care and safety. In this paper, two technologies are developed and applied for the proposed wearable electronic shoes design, which are 3D customized shoes design with data mining, location tracking function with GPS and RFID technologies respectively. The proposed technologies are integrated and applied in the prototypes with the customized shoes design. The newly developed smart shoes were successfully prototyped. It demonstrated that the proposed shoes do not only provide the elderly foot care service with customized smart design but also the elderly safety service with location tracking function effectively.